2010
DOI: 10.1016/j.jada.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sources of Sodium in China, Japan, the United Kingdom, and the United States, Women and Men Aged 40 to 59 Years: The INTERMAP Study

Abstract: Public health campaigns in several countries encourage population-wide reduced sodium (salt) intake, but excessive intake remains a major problem. Excessive sodium intake is independently related to adverse blood pressure and is a key factor in the epidemic of prehypertension/ hypertension. Identification of food sources of sodium in modern diets is critical to effective reduction of sodium intake worldwide. We used data from the INTERMAP Study to define major food sources of sodium in diverse East Asian and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
412
3
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 467 publications
(440 citation statements)
references
References 37 publications
16
412
3
9
Order By: Relevance
“…1 Although the exact causes and mechanisms of hypertension are not known, it is generally believed that both genetic 12,13 and environmental factors, such as dietary salt, adiposity, cigarette smoking and mental stress were involved in determining the levels of BP and the prevalence of hypertension. [14][15][16] Knowledge of the prevalence of hypertension and the extent to which it is being detected, treated and controlled are essential to understand the magnitude of the problem and how well it is being addressed. In Tunisia, there were limited data about the prevalence of hypertension, 11,17,18 with no national estimates and no information about the levels of awareness, treatment and control of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although the exact causes and mechanisms of hypertension are not known, it is generally believed that both genetic 12,13 and environmental factors, such as dietary salt, adiposity, cigarette smoking and mental stress were involved in determining the levels of BP and the prevalence of hypertension. [14][15][16] Knowledge of the prevalence of hypertension and the extent to which it is being detected, treated and controlled are essential to understand the magnitude of the problem and how well it is being addressed. In Tunisia, there were limited data about the prevalence of hypertension, 11,17,18 with no national estimates and no information about the levels of awareness, treatment and control of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…While we did not analyse meal patterns and their sodium contribution to the total daily intake, a previous Australian study found that lunch had the highest sodium density compared to dinner and breakfast [29]. Our study did not assess the use of discretionary salt, but in low and low-middle income countries, this has been found to be a significant source of sodium which may account for up to 76% of total intake in China [13].…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, sources of sodium may vary in other countries depending on the major foods consumed and cultural context. For instance, in Japan, most of the dietary sodium is derived from soy sauce, salted soups, processed fish/ seafood and preserved vegetables [13]. While we did not analyse meal patterns and their sodium contribution to the total daily intake, a previous Australian study found that lunch had the highest sodium density compared to dinner and breakfast [29].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, according to the distribution of mean dietary sodium intake, the mean dietary salt intake by Japanese patients with type 2 diabetes was 10.7 g/d,8 and their intake was lower than that in the general Japanese population (11.7 g/d)19 and higher than that in the US and UK general populations (9.1 and 8.6 g/d, respectively),20 as well as a diabetic population in the United States (6.4–8.6 g/d) 21. Therefore, based on the current situation of dietary salt intake by countries, it is reasonable that the goals for daily intake of dietary salt in guidelines are below 6 g/d for Western diabetic patients regardless of the presence or absence of hypertension and/or diabetic complications although a clearly numerical target (<6 g/d) was set only for patients with diabetes having hypertension and/or diabetic complications in Japan.…”
Section: What Are the Current Status And Issues Of Leading Guidelinesmentioning
confidence: 92%